2014
DOI: 10.1091/mbc.e13-09-0530
|View full text |Cite
|
Sign up to set email alerts
|

Caenorhabditiseleganschaperonin CCT/TRiC is required for actin and tubulin biogenesis and microvillus formation in intestinal epithelial cells

Abstract: Caenorhabditis elegans chaperonin CCT is required for the biogenesis of actin and tubulin and is thereby essential for microvillus formation in intestinal cells. Loss of CCT/TRiC had no strong effects on intermediate filament protein IFB-2 or cytoskeletal linker protein ERM-1, suggesting that CCT/TRiC exhibits clear substrate specificity in living animals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
48
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 55 publications
4
48
0
Order By: Relevance
“…One paper has addressed the role of the cytosolic CCT/TRiC chaperonin in the intestine (Saegusa et al, 2014); other chaperonins of the CCT and prefoldin families have been showed to affect MTs in the epidermis (Quintin et al, 2016).…”
Section: Chaperoninsmentioning
confidence: 99%
See 4 more Smart Citations
“…One paper has addressed the role of the cytosolic CCT/TRiC chaperonin in the intestine (Saegusa et al, 2014); other chaperonins of the CCT and prefoldin families have been showed to affect MTs in the epidermis (Quintin et al, 2016).…”
Section: Chaperoninsmentioning
confidence: 99%
“…The establishment and maintenance of polarity is highly dependent on protein recycling at the plasma membrane (Shivas et al, 2010). Protein recycling is a two-step process whereby proteins are first subjected to internalization through clathrin-dependent endocytosis or clathrin-independent endocytosis (Goldenring, 2015;Sato et al, 2014). Once internalized, these endocytic vesicles are delivered to peripheral organelles known as sorting endosomes, also called early endosomes.…”
Section: Noncentrosomal Microtubules Motor Proteins and Recycling Enmentioning
confidence: 99%
See 3 more Smart Citations